PENGARUH LOCUS OF CONTROL, PERATURAN TENTANG PENGGUNAAN INTERNET, DAN NORMA YANG BERLAKU PADA REKAN KERJA SERTA PIMPINAN TERHADAP PERILAKU CYBERLOAFING PADA KARYAWAN UNIVERSITAS DHARMA ANDALAS - Hastini, Lasti Yossi (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
The purpose of this study is to find out the applicable regulations on internet usage at Dharma Andalas University, to provide empirical evidence of the influence of internal and external locus of control on cyberloafing behavior, to provide empirical evidence of influence of the norms that are adopted by colleagues and leaders of cyberloafing behavior; to provide empirical evidenceof the influence of locus of control and the norms that are adopted by colleagues and leaders of cyberloafing behavior. This research is a correlational quantitative research that is intended to know whether there is a relationship between two or several variables. Data collection techniques were conducted by distributing questionnaires by census. There are 35 respondents who are employees of Dharma Andalas University. To analyze the data used SPSS application. The results obtained show that there is no written and binding regulation related to internet usage at Dharma Andalas University; the internal locus of control has no significanteffect on cyberloafing behavior; norms that are adopted by colleagues and leaders have a significant effect on cyberloafing behavior; and locus of control and norms that are adopted by colleagues and leaders simultaneously have a significant effect on cyberloafing behavior.Keywords: cyberloafing, locus of control, internet usage rules, norms